The current status of governance on Waqf sector in Indonesia - Listiana, Lisa; Al-Hidabi, Dawood Abdulmalek Yahya (2018)
Purpose In the past, waqf was able to significantly contribute towards the ummah welfare. While the potential remains in this contemporary era, a contrast situation on waqf can be observed in many Muslim countries, including Indonesia. In Indonesia, most of existing waqf assets are not productive. Yet the actual collection of cash waqf is reported to be less than 1% of its perceived potential. National Planning Agency (BAPPENAS) mentioned that this situation occurred due to lack of transparency and good governance on waqf sector in Indonesia. Whereas some studies have acknowledged importance of effective governance for waqf revival, a study that elaborates the current status of governance on this sector is hardly found. The current study aims to elaborate and analyze the reality of governance of waqf sector in Indonesia. Design/methodology/approach Qualitative approach with meta-synthesis of the literatures on governance and waqf in Indonesia is employed in this study. In addition, relevant laws, regulations, published reports, and online sources are also being included. Findings According to Waqf Act 41/2004, Indonesian Waqf Board (IWB) represents the governing body of waqf sector in Indonesia. Theoretically, this body is equipped with certain authorities and resources to conduct the governance mechanism. However, in practice, lack of governance mechanism and issue on governance structure are observed. In addition, Ministry of Religious Affairs (MoRA) is also playing a role as Waqf authority in the country. Lack of explicit work clarity and segregation of duties between those two authorities is considered to cause overlap and inefficiency in governance of waqf sector in Indonesia. Hence, clear governance system of waqf sector in term of functioning (mechanism), structure, infrastructure, and composition are in need of development and implementation. Originality/value This study represents the first work that attempts to elaborate the state of governance of Waqf sector in Indonesia